Silurian tectonic history of Penobscot Bay region, Maine - Stewart, David; Unger, John; Hutchinson, Deborah (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1995)
Early Paleozoic amalgamation of composite terrancs was contemporaneous at widely separated regions that were later accreted to either ancestral North America or to Gondwana as those two continents approached each other. Terranes closer to Laurentia amalgamated in the Late Cambrian to Middle Ordovician Penobscottian orogeny and were accreted to ancestral North America in the Middle and to Late Orodovician Taconic orogeny. Peri-Gondwanan terranes formed from Late Cambrian and Early Ordovician rocks were amalgamated in the Late Ordovician and Early Silurian to form the Salinic orogenic belt, now exposed from western Europe to southern New England. Salinic orogenic activity involved extensive thrust faulting and metamorphism, large strike-slip faults, and plutonism, all of which are represented in coastal Maine. In the Penobscot Bay region, Maine, the peri-Gondwanan St. Croix terrane was thrust northwest in the Silurian(?) upon middle amphibolite facies Ordovician and Early Silurian rocks of the Fredericton trough. Seismic reflection profiles show that the thrust fault dips southeasterly at -30° and becomes listric at about 13 ± 2 km. The thrust sheet was broken initially by the Late Silurian Penobscot Bay-Smith Cove-North Blue Hill dextral strike-slip fault which juxtaposed the peri-Gondwanan Ellsworth terrane, followed by emplacement of the South Penobscot Intrusive Suite and by a sequence of strike-slip fault zones each with up to 20 km of dextral Silurian and Early Devonian(?) movement. The strike-slip faults are interpreted to either remain steep until they reach the sole of the thrust sheet or to become listric within the thrust sheet. In the Devonian Acadian orogeny, more outboard terranes with Gondwanan affinities, like the Avalonian terranes in southern New Brunswick and in eastern Massachusetts, were amalgamated with the Silurian orogenic belt, and the resulting composite terrane was accreted to ancestral North America. Acadian deformation, mcta-morphism, and plutonism are superimposed on the Silurian orogen, blurring or obliterating the evidence of Silurian orogeny.